Pages into Speech : instruction and training manual for 3rd-year students of the School of Foreign Languages [Electronic resourсe] - Пахаренко, Анастасія Валентинівна; Вакуленко, Анастасія Ігорівна; Pakharenko, Anastasiia; Vakulenko, Anastasiia (Kharkiv : V. N. Karazin Kharkiv National University, 2026)
"Pages into Speech" is designed for third-year students of the School of Foreign Languages at V. N. Karazin Kharkiv National University, majoring in Philology and Secondary Education (English). The manual supports the development of advanced speaking skills within the courses Foreign Language I and II in accordance with current curriculum requirements.The thematic focus covers literature and education through units such as Reading, Books, Writers, School Education, and Students. The materials encourage reflection on literary genres, the social role of books and writers, and contemporary academic experience, providing meaningful contexts for structured oral practice. Each unit progresses from input to interaction and includes text- or media-based prompts, vocabulary tasks, discussions, problem-solving activities, and presentations. Based on communicative principles, the manual fosters fluency, accuracy, critical thinking, and discourse management. It can be used both in classroom instruction and for independent study.

"Від Тексту до Мовлення" призначений для студентів третього курсу факультету іноземних мов Харківського національного університету імені В. Н. Каразіна спеціальностей «Філологія» та «Середня освіта (Англійська мова)». Посібник спрямований на розвиток навичок усного мовлення в межах дисциплін «Іноземна мова I» та «Іноземна мова II» відповідно до чинної освітньої програми. Тематика охоплює літературу й освіту та реалізується через розділи Читання, Книги, Письменники, Шкільна Освіта, Студенти. Матеріали сприяють осмисленню жанрів, ролі книги й письменника в суспільстві та сучасного освітнього досвіду, створюючи змістовну основу для розвитку усного мовлення. Структура розділів передбачає перехід від аналізу тексту чи медіаматеріалу до інтерактивної діяльності: лексичних вправ, дискусій, проблемних завдань і мініпрезентацій. Посібник ґрунтується на комунікативному підході та може використовуватися як на практичних заняттях, так і для самостійної роботи.
Від Тексту до Мовлення : навчально-методичний посібник для студентів 3 курсу факультету іноземних мов [Електронний ресурс]
Електронне навчальне видання комбінованого використання. Можна використовувати в локальному та мережному режимі. В авторській редакції
Keywords: HUMANITIES and RELIGION::Languages and linguistics::Other Germanic languages::English language; SOCIAL SCIENCES::Social sciences::Education::Subject didactics; advanced speaking skills; communicative approach; critical thinking; discourse management; literature and education; дискурсивна компетентність; комунікативний підхід; критичне мислення; література та освіта; усне мовлення